Central bank independence and wage bargaining structure: Empirical evidence - Juha Kilponen (Bank of Finland, 1999)
This paper studies the relationship between central bank independence, wage bargaining structure and macroeconomic performance in OECD countries.A cross-sectional time-series (TSCS) model for inflation, nominal wage growth and unemployment for the period 1973-1996 is estimated using different and updated measures of central bank independence.The importance of the price stability objective in the central bank statute is used as a proxy for the degree of conservativeness of the central bank.A recently published data set on wage bargaining structure is used, and a distinction is made between coordination of wage bargaining and formal centralization.A new measure of union power is constructed, which combines formal centralization and union density.The implications of the large differences that can be seen between coverage and unionization rates in some countries are briefly discussed.Two important results emerge.First, the central bank's political independence and personnel independence contribute most importantly to a successful inflation policy.Second, a high level of coordination contributes to moderate inflation rates and unemployment, while union monopoly power tends to increase inflation.
URN:NBN:fi:bof-20140807173
Keywords: 330